The Impact of Green Accounting Implementation and Carbon Emission Disclosure on Company Value - Dwiananda, Ni Kadek Dina; Wirawati, Ni Gusti Putu (Dinasti Publisher, 2025)
This study examines the relationship between the implementation of green accounting and the disclosure of carbon emissions and the value of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2021–2023. The foundation of this study is the significance of environmental sustainability in corporate operations, particularly in sectors that generate necessities for the community. Implementing green accounting and carbon emission disclosure can help companies achieve their goal of increasing their value by improving their reputation with investors and the general public. This study used panel data samples and multiple linear regression analysis. Purposive sampling methods were used to choose 56 businesses as samples. Based on sustainability and the company's annual report, 168 observations were made. This study indicates that implementing green accounting and carbon emission disclosure greatly raises the company's worth.